Analysis of factor VIII mediated suppression of lentiviral vector titres - Radcliffe, P A; Sion, C J M; Wilkes, F J; Custard, E J; Beard, G L; Kingsman, S M; Mitrophanous, K A (Gene therapy, 2008)
Effective gene therapy for haemophilia A necessitates a vector system that is not subject to a pre-existing immune response, has adequate coding capacity, gives long-term expression and preferably can target non-dividing cells. Vector systems based on lentiviruses such as equine infectious anaemia virus (EIAV) fulfil these criteria for the delivery of factor VIII (FVIII). We have found that B domain-deleted (BDD) FVIII protein inhibits functional viral particle production when co-expressed with the EIAV vector system. Although particle numbers (as measured by reverse transcriptase activity) are near normal, RNA genome levels are reduced and measurement of integrated copies revealed the virus is severely defective in its ability to transduce target cells. This is due to the absence of sufficient vesicular stomatitis virus glycoprotein (VSV-G) envelope on viral particles derived from cells expressing FVIII. By using an internal tissue-specific promoter, that has low activity in the producer cells, to drive expression of FVIII we have overcome this inhibitory effect allowing us to generate titres approaching those obtained with vector genomes encoding reporter genes. Furthermore, we report that codon optimization of the full-length FVIII gene increased vector titres approximately 10-fold in addition to substantially improving expression per integrated vector copy.